Financial crisis, global liquidity and monetary exit strategies - Ansgar Belke (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We develop a roadmap of how the ECB should further reduce the volume of money (money supply) and roll back credit easing in order to prevent inflation. The exits should be step-by-step rather than one-off. Communicating about the exit strategy must be an integral part of the exit strategy. Price stability should take precedence in all decisions. Due to vagabonding global liquidity, there is a strong case for globally coordinating monetary exit strategies. Given unsurmountable practical problems of coordinating exit with asymmetric country interests, however, the ECB should go ahead - perhaps joint with some Far Eastern economies. Coordination of monetary and fiscal exit would undermine ECB independence and is also technically out of reach within the euro area.
Keywords: E52; E58; F42; E63; 330; Exit strategies; international policy coordination and transmission; open market operations; unorthodox monetary policy; Finanzmarktkrise; Gesamtwirtschaftliche Liquidität; Geldpolitik; Internationale wirtschaftspolitische Koordination; Geldmenge; Inflationsbekämpfung; EU-Staaten; Welt